Development of Identification Instruments for Children with Specific Learning Disability in Elementary School - Salma Nadiyah; Budi Susetyo; Iding Tarsidi; Ranti Novianti; Ediyanto Ediyanto; Sinta Yuni Susilawati; Yoga Budhi Santoso (Journal of ICSAR, 2022)
This study aims to facilitate the identification of students in elementary school who have specific learning dissability. This study employs a qualitative approach to the literature review process. The study collected data from books and articles that discuss identifying specific learning dissability. The data collection technique is based on a literature review of scientific books and journals and interviews with professional practitioners and academics, subsequently validated. The findings of this study are presented in the form of a draft identification guide for elementary school-aged children with specific learning dissability. Teachers and parents can easily use the draft guidelines for identifying children with specific learning dissability because they are presented concisely and clearly that refers to the theory and validated by four validators, including psychologists, special education lecturers, and inclusive school and special education teachers. The identification guideline draft for children with specific learning dissability in elementary school-age includes procedures for identifying children with specific learning dissability in general and instruments for identifying children with dyslexia, dyscalculia, and dysgraphia. This procedure was proposed to assist teachers and parents in identifying children with specific learning dissability in elementary school.